1980
DOI: 10.1152/jappl.1980.49.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and heart rate during treadmill exercise in the Marabou stork

Abstract: Oxygen consumption (VO2), heart rate, body temperature, and stride frequency were measured in Marabou storks walking on a treadmill at a range of speeds and gradients. VO2 was linearly related to speed at gradients up to 11 degrees and speeds up to 1.4 m . s-1, and the slope of the VO2/speed regression increased with the treadmill angle up to 9 degrees. At 11 degrees there was a fall in the slope. Analysis indicates the cost of horizontal movement of about 1.1 ml O2 . m-1 (mean wt 4.5 kg). The cost of vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…The increase in metabolic cost when moving up an incline agrees with previous studies (Armstrong et al, 1983;Bamford and Maloiy, 1980;Bedford et al, 1979;Brooks and White, 1978;Chassin et al, 1976;Clapperton, 1964;Cohen et al, 1978;Dill, 1965;Eaton et al, 1995;Ellerby et al, 2003;Farley and Emshwiller, 1996;Margaria et al, 1963;McDonough et al, 2002;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Rubenson et al, 2006;Snyder and Carello, 2008;Taylor et al, 1972;Warncke et al, 1988;White and Yousef, 1978;Wickler et al, 2000;Wickler et al, 2003;Wunder and Morrison, 1974;Yousef et al, 1972). The finding that descending a decline is not metabolically cheaper than locomoting on the level, however, is contrary to previous findings (Armstrong et al, 1983;Byrnes et al, 1985;Cohen et al, 1978;Margaria et al, 1963;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Taylor et al, 1972;White and Yousef, 1978;Yousef et al, 1972).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The increase in metabolic cost when moving up an incline agrees with previous studies (Armstrong et al, 1983;Bamford and Maloiy, 1980;Bedford et al, 1979;Brooks and White, 1978;Chassin et al, 1976;Clapperton, 1964;Cohen et al, 1978;Dill, 1965;Eaton et al, 1995;Ellerby et al, 2003;Farley and Emshwiller, 1996;Margaria et al, 1963;McDonough et al, 2002;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Rubenson et al, 2006;Snyder and Carello, 2008;Taylor et al, 1972;Warncke et al, 1988;White and Yousef, 1978;Wickler et al, 2000;Wickler et al, 2003;Wunder and Morrison, 1974;Yousef et al, 1972). The finding that descending a decline is not metabolically cheaper than locomoting on the level, however, is contrary to previous findings (Armstrong et al, 1983;Byrnes et al, 1985;Cohen et al, 1978;Margaria et al, 1963;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Taylor et al, 1972;White and Yousef, 1978;Yousef et al, 1972).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have found the slope of the line of best fit between V O2 and U to increase with gradient (Armstrong et al, 1983;Bamford and Maloiy, 1980;Chassin et al, 1976;Clapperton, 1964;Cohen et al, 1978;Eaton et al, 1995;Farley and Emshwiller, 1996;Full and Tullis, 1990;Margaria et al, 1963;McDonough et al, 2002;Raab et al, 1976;Robbins et al, 1979;Taylor et al, 1972;Warncke et al, 1988;White and Yousef, 1978;Wunder and Morrison, 1974;Yousef et al, 1972) and the established way of calculating the efficiency of moving along gradients for comparison between different species is dependent upon there being a difference (Taylor et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research in this field has focused on level treadmill locomotion, with relatively few studies examining the potential effects of inclines (Bamford and Maloiy, 1980;Ellerby et al, 2003;Rubenson et al, 2006;Snyder and Carello, 2008;Warncke et al, 1988). Examining the cost of incline locomotion is important and relevant as organisms seldom experience steady-state conditions, being faced with variable terrain over which energy demands for locomotion are continuously changing.…”
Section: Introductionmentioning
confidence: 99%
“…During terrestrial locomotion, a bird's rate of energy metabolism, the cost of locomotion, increases as a function of speed (U) until a morphological (mechanical) or physiological (energetic) constraint is met (Brackenbury and Avery 1980;Roberts et al 1998;Nudds et al 2010). This increase is often linear (Pinshow et al 1977;Bamford and Maloiy 1980;Taylor et al 1982;Brackenbury and Elsayed 1985;Roberts et al 1998;White et al 2008); however, nonlinearity within and between gaits is also common (Rubenson et al 2004(Rubenson et al , 2007Watson et al 2011;Nudds et al 2011). Elevated energy metabolism at faster U correlates with shorter periods of foot-ground contact, which require higher rates of force production by muscle fibres (Kram and Taylor 1990;Roberts et al 1998).…”
Section: Introductionmentioning
confidence: 99%